The Dilemmas of Solidarity of Civic Activists: Supporting Displaced Ukrainians in a Non‐Solidarian Regime - Violetta Zentai; Margit Feischmidt (Social Inclusion)
Civic actors working with marginalized and disadvantaged groups in society face various dilemmas associated with defining and, if needed, ranking human needs and vulnerabilities. Our article examines the reasonings for intervention in civic solidarity operations that emerged in response to the arrivals of displaced Ukrainians in Hungary in 2022–2023. Solidarians have strived to find spaces of action in an authoritarian regime that normalizes policy rationales of deservingness and social hierarchy in contrast to equality and inclusion‐based diversity. We engaged with those solidarity actors who showed some degree of reflexivity to the wider social, political, governance, and charity activism landscapes considering their position and operational ethos. The mixed research methods generated ethnographic and discursive data that allow us to offer a practice‐centered interpretation of civic actors’ reasoning. This article explores the dilemmas that civic actors face when judging and prioritizing needs, responsibilities, and resources in comparing and contrasting the conditions of their own society and the situation of people with migratory trajectories. We identified three perspectives through which civic solidarity actors articulated their normative and strategic dilemmas: the origin and nature of the needs of the displaced people, the refugee assistance responsibilities thereby assigned, and the broader social care system in the host society. We offer insights into how solidarity actors discernibly departed from pure humanitarianism and deployed concepts of horizontal interdependence, anti‐discrimination, and layered human rights, applying their own vocabularies.